Anomalous periodicity in superpositions of localized periodic patterns. (1st July 2022) - Amit, Omer; Dobkowski, Or; Zhou, Zhifan; Margalit, Yair; Japha, Yonathan; Moukouri, Samuel; Meir, Yigal; Horovitz, Baruch; Folman, Ron
Abstract: Interference between overlapping periodic patterns gives rise to important phenomena, such as Moiré fringes, appearing when the patterns have different periods or orientations. Here we present a novel phenomenon, applicable to both the classical and quantum regimes, where two one-dimensional localized periodic patterns with the same period interfere to create fringes with anomalous periodicity. We analyze the effect theoretically and demonstrate it with atomic matter waves. When a central parameter of the system is scanned continuously, we observe a discontinuous but piecewise-rigid periodicity of the resulting fringes. We show that this is a universal phenomenon that emerges from a superposition of two spatially shifted localized periodic patterns of any source or nature when they interfere with a global phase difference. The rigidity of the spectrum becomes even more robust for a coherent superposition of non-overlapping wavepackets, although the conventional interferometric visibility drops to zero. The effect is expected to appear in space and time, as well as in the momentum distribution of quantum particles.